The Role of Organizational Citizenship Behavior (OCB), Perceived Organizational Support (POS) on SMEs Performance by Mediation of Organizational Commitment - Elyzabeth Wijaya (International Journal of Artificial Intelligence Research, 2022)
The aim of this study is to analyze the relationship between organizational citizenship behavior (OCB) on organizational commitment, organizational citizenship behavior (OCB) on SMEs performance, perceived organizational support (POS) on organizational commitment, perceived organizational support (POS) on SMEs performance, organizational commitment on SMEs performance. Organizational Citizenship Behavior (OCB) on SMEs Performance through mediation of organizational commitment, perceived organizational support (POS) on SMEs performance through mediation of organizational commitment.This study used a quantitative method, the respondents of this study were 380 UKM owners who were determined by the simple random sampling method. Online questionnaire questions are provided with answer options with rules based on a 5-point Likert scale. Online questionnaires were distributed to respondents using social media. All answers are tabulated for further processing to obtain results and conclusions. Data analysis in this study used structural equation modeling (SEM) with smartPLS 4.0 software tools. The stages of data testing are data validation and reliability tests and hypothesis testing.The variable of this research is the independent variable Organizational Citizenship Behavior (OCB), Perceived Organizational Support (POS). The dependent variable is SME Performance and the mediating variable is Organizational Commitment. The results of this study indicate that organizational citizenship behavior (OCB) has a positive and significant effect on organizational commitment, organizational citizenship behavior (OCB) has a positive and significant effect on SMEs performance, perceived organizational support (POS) has a positive and significant effect on organizational commitment , perceived organizational support (POS) has a positive and significant effect on SMEs performance, organizational commitment has a positive and significant effect on SMEs performance. Organizational Citizenship Behavior (OCB) has a positive and significant effect on SMEs Performance through mediation of organizational commitment, perceived organizational support (POS) has a positive and significant effect on SMEs performance through mediation of organizational commitment. Keywords: Organizational Citizenship Behavior (OCB), Perceived Organizational Support (POS), SME Performance, Organizational Commitment